2014
DOI: 10.1371/journal.pone.0109674
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights into the Interaction between Plasmodium falciparum Apical Membrane Antigen 1 and an Invasion-Inhibitory Peptide

Abstract: Apical membrane antigen 1 (AMA1) of the human malaria parasite Plasmodium falciparum has been implicated in invasion of the host erythrocyte. It interacts with malarial rhoptry neck (RON) proteins in the moving junction that forms between the host cell and the invading parasite. Agents that block this interaction inhibit invasion and may serve as promising leads for anti-malarial drug development. The invasion-inhibitory peptide R1 binds to a hydrophobic cleft on AMA1, which is an attractive target site for sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…Unlike the longer RON2sp1 peptide, RON2hp leaves most of the hydrophobic cleft free. The disulfide‐bridge is positioned toward the centre of the hydrophobic cleft that has been identified as the primary hot spot for small‐molecule binding, and thus offers an ideal site for Cys specific spin‐labelling to confer PRE effects on molecules bound to the cleft. The highly conserved disulfide bridge between Cys2037 and Cys2049 helps stabilise an anti‐parallel β‐hairpin structure for the peptide .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the longer RON2sp1 peptide, RON2hp leaves most of the hydrophobic cleft free. The disulfide‐bridge is positioned toward the centre of the hydrophobic cleft that has been identified as the primary hot spot for small‐molecule binding, and thus offers an ideal site for Cys specific spin‐labelling to confer PRE effects on molecules bound to the cleft. The highly conserved disulfide bridge between Cys2037 and Cys2049 helps stabilise an anti‐parallel β‐hairpin structure for the peptide .…”
Section: Resultsmentioning
confidence: 99%
“…Computational studies on AMA1 structures identified a druggable hydrophobic pocket (≈420 Å 3 solvent‐accessible volume) in the cleft as the primary hot spot for small‐molecule binding . The pocket is surrounded by polar residues with a hydrophobic base composed of Ile252, Phe367 and Phe274, flanked by Tyr251 at one end and by Met273 at the other . Again, the conformation adopted by 3D7 Pf AMA1 upon RON2sp1 binding (PDB ID: 3ZWZ) revealed a pocket surrounded by Met224, Phe183, Tyr236 and Tyr251 in the centre of the hydrophobic cleft .…”
Section: Resultsmentioning
confidence: 99%
“…However, upon binding to AMA1, the chemical shift difference between the two resonances increases and the further downfield resonance is broader. We infer that the further downfield and broader peak in Figure 5b arises from Phe5 and the less shifted and sharper peak from Phe2 on the basis of mutational data on R1 [57,58] and the crystal structure of the R1-AMA1 complex [59], in which Phe5 makes more significant contact with AMA1 than does Phe2. Indeed, Phe2 can be omitted in truncated analogues of R1 without significant loss of binding affinity [57,58], whereas Phe5 Although the examples above (Figures 4 and 5) illustrate the application of 19 F-NMR to characterising peptide-protein interactions rather than the interactions of elaborated fragments with proteins, both of the proteins exemplified, SPSB2 and AMA1, have been the subject of FBDD campaigns and the peptides have been valuable in confirming the binding sites of fragments and elaborated fragments on the target proteins.…”
Section: Ligand Binding Site Mappingmentioning
confidence: 84%
“…However, upon binding to AMA1, the chemical shift difference between the two resonances increases and the further downfield resonance is broader. We infer that the further downfield and broader peak in Figure 5b arises from Phe5 and the less shifted and sharper peak from Phe2 on the basis of mutational data on R1 [57,58] and the crystal structure of the R1-AMA1 complex [59], in which Phe5 makes more significant contact with AMA1 than does Phe2. Indeed, Phe2 can be omitted in truncated analogues of R1 without significant loss of binding affinity [57,58], whereas Phe5 is essential.…”
Section: Ligand Binding Site Mappingmentioning
confidence: 84%
See 1 more Smart Citation